Highly active anode electrocatalysts derived from electrochemical leaching of Ru from metallic Ir0.7Ru0.3 for proton exchange membrane electrolyzers. (April 2017) - Wang, Li; Saveleva, Viktoriia A.; Zafeiratos, Spyridon; Savinova, Elena R.; Lettenmeier, Philipp; Gazdzicki, Pawel; Gago, Aldo S.; Friedrich, K. Andreas
Abstract: Hydrogen produced by water splitting is a promising solution for a sustained economy from renewable energy sources. Proton exchange membrane (PEM) electrolysis is the utmost suitable technology for this purpose, although the quest for low cost, highly active and durable catalysts is persistent. Here we develop a nanostructured iridium catalyst after electrochemically leaching ruthenium from metallic iridium-ruthenium, Ir0.7 Ru0.3 Ox (EC), and compare its physical and electrochemical properties to the thermally treated counterpart: Ir0.7 Ru0.3 O2 (TT). Ir0.7 Ru0.3 Ox (EC) shows an unparalleled 13-fold higher oxygen evolution reaction (OER) activity compared to the Ir0.7 Ru0.3 O2 (TT). PEM electrolyzer tests at 1 A cm −2 show no increase of cell voltage for almost 400 h, proving that Ir0.7 Ru0.3 Ox (EC) is one of the most efficient anodes so far developed. Graphical abstract: Highlights: Novel oxygen evolution catalyst is developed by electrochemical leaching of Ru from metallic Ir0.7 Ru0.3 . The material shows an unprecendented 13-fold higher activity compared to the state-of-the-art Ir0.7 Ru0.3 O2 . Highly porous oxy-hydroxide surface is revealed by XRD, TEM, STEM, and near-ambient pressure XPS. MEA test in PEM electrolyzer confirmed the high performance and stability of the Ru-leached Ir anode.